Delineation of thickness of intrabasaltic rocks beneath the Deccan Volcanic province of western India through microtremor analysis. Issue 138 (November 2020) - Singh, A.P.; Sairam, B.; Pancholi, Vasu; Chopra, Sumer; Kumar, M. Ravi
Abstract: This study presents the results of microtremor investigations conducted to determine the shallow subsurface structure of the Saurashtra horst, which was strongly affected by the episodes of Deccan volcanism during the Paleocene Epoch. Measurements of microtremor were carried out at 100 sites using single station and 10 sites using an array, distributed over the Saurashtra peninsula. We used horizontal - to - vertical spectral ratio (HVSR) of the microtremor to determine resonant frequencies at each site. The HVSR curves corresponding to the Deccan trap formations show a plateau like shape with no sharp peak. Our results also show that the average predominant frequencies are 0.82 Hz for Dwarka and 1.0 Hz for Miliolite formations. The analysis suggests that the thickness of the uppermost layers varies from 8 to 12 m, with a low shear wave velocity ranging from 175 to 400 m/s, which corresponds to thin soft sediments or a highly weathered rock. The second layer, down to depths of 25–40 m with shear wave velocity of 450–800 m/s corresponds to a layer of intrabasaltic beds. The third layer has shear wave velocity ranging from 850 to 1350 m/s down to a depth of 70–80 m. The estimated thickness of the intrabasaltic bole varies from 34 to 40 m. Furthermore, the estimated thickness of the Miliolite and the Dwarka formations is 90 m and 250 m, respectively. The results of the single station and array measurements were compared with the results of the MASW and well-log data for validation of the results. Highlights: Determine the shallow subsurface structure of the Saurashtra horst (India). HVSR curves corresponding to the Deccan trap formations show a plateau like shape with no sharp peak. Average predominant frequencies are 0.82 Hz for Dwarka and 1.0 Hz for Miliolite formations. Estimated thickness of the intrabasaltic bole varies from 34 to 40 m. Estimated thickness of the Miliolite and the Dwarka formations is 90 m and 250 m, respectively.